Students' Scientific Literacy and Critical Thinking Skills: A Pre-Post Study on the Implementation of GI-MM - Pujiastuti, Indah Panca; Fausan, Muhammad Mifta (Journal of Education Research, 2024)
University-level learning is currently aimed at encouraging students to master high-level skills such as scientific literacy and critical thinking skills. This study aimed to determine the differences in scientific literacy and critical thinking among students before and after being taught using the Group Investigation-Mind Mapping (GI-MM) model. This quasi-experimental study used a one-group pretest-posttest design. The study population comprised of 55 students enrolled in a biochemistry course. Using the cluster random sampling technique, one class (19 students) was selected as the research sample. The instruments used in this study were multiple-choice written test questions to measure students' scientific literacy, and essay-type written test questions to measure students' critical thinking. Descriptive and inferential analyses were used for data analysis (paired t-test). The results showed that all indicators of students' scientific literacy improved after implementation of the GI-MM model, with an average increase of 40.04%. In addition, the mean pretest and posttest scores for the five indicators of students' critical thinking showed significant improvement after implementation of the GI-MM learning model, with an average increase of 61.43%. The paired t-test results reinforced the finding that there were significant differences in the students' scientific literacy and critical thinking skills before and after being taught using the GI-MM learning model.